Educator Management Policy from the Perspective of Education Law: Between Professionalism and Rights Protection - Rhamdani; Pepriyani (PT. Meja Ilmiah Publikasi, 2026)
This article examines how educational management can operate as a governance mechanism for fulfilling and protecting students' rights within Indonesian education law following the 2026 Safe and Comfortable School Culture reform. The study uses normative legal research combining statutory and conceptual approaches with a structured purposive review of relevant scholarship. The analysis maps legal bases, duty-bearers, managerial functions, implementation mechanisms, and auditable evidence. The findings organize students' rights into access and continuity, equality, safety, reasonable accommodation, participation, and accessible complaint and remedy. From this synthesis, the article proposes a Rights-Based School Governance (RBSG) model with six parallel dimensions: legal alignment and rights mapping; inclusive planning and equitable resource allocation; a safe and dignified learning environment; meaningful student participation; accessible complaint, response and remedy; and rights-based monitoring, evaluation and accountability. The model translates legal duties into process ownership, documentary evidence, proportional safeguards, and review triggers while also recognizing procedural protection for educators. RBSG is a normative construction rather than an empirically validated intervention. Its feasibility, administrative burden, indicator validity, and effects on safety, inclusion, trust in complaint mechanisms, and continuity of learning therefore remain propositions for future multi-site empirical testing.